Hypoglycemic and anticataract activity of crude exopolysaccharides of medicinal mushroom Phellinus badius on streptozotocin-induced diabetic rats and goat eye lenses respectively. (October 2020) - Sonawane, Hiralal; Arya, Sagar; Ghole, Vikram; Apte, Kishori; Shelke, Deepak; Chaskar, Manohar
Abstract: Phellinus badius is one of the medicinal mushrooms used as folk medicine in Western Ghats of India. Traditionally, the P. badius is used in the treatment of diabetes, diarrhea, arthritis, toothaches, as well as tongue and throat related ailments. Therefore, we investigated the hypoglycemic and anticataract activity of P. badius crude exopolysaccharides (EPS) in streptozotocin (STZ) induced diabetic rats and Goat eye lens, respectively. The EPS obtained from the submerged mycelial culture of P. badius was used for the bioactivity studies. Among various concentrations of EPS administered to diabetic rats, 400 mg/kg dose showed significant hypoglycemic effects, such as the reduction in blood glucose (37.2 %) and increase in body weight (47.4 %) as compared to the control groups. Furthermore, reduction in triglycerides (23.4 %), cholesterol (23.4 %), as well as decrease in the activities of aspartate aminotransferase (33.8 %) and alanine aminotransferase (31.9 %) were also observed. The crude EPS retarded the progression of lens opacification and reduced the risk of cataract formation in sugar administered goat eye lenses. The results suggest that the crude EPS obtained from P. badius mycelia can be considered as a potential source for hypoglycemia and cataractogenesis. The LC/MS analysis revealed the metabolic profile of the crude EPS, which could be further evaluated based on bioassay guided fractionation to identity and characterize the active ingredients. Graphical abstract: Hypoglycemic and anticataract activity of Phellinus badius crude exopolysaccharides. Image 1 Highlights: Crude exopolysaccharides (EPS) were obtained from the in vitro mycelial culture of P . badius . EPS treatment alleviated the hyperglycemia in streptozotocin-induced diabetic rats. EPS protected the Goat eye lenses from cataractogenesis in in vitro conditions. LC/MS analysis of crude EPS revealed the presence of bioactive compounds.